1998
DOI: 10.1037/0022-3514.75.6.1528
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for sex and risky sexual behavior among adolescents and young adults: A functional perspective.

Abstract: The implications of a functionalist perspective for understanding sexual risk taking are explored. Key motivational dimensions thought to underlie human behavior (viz., approach vs. avoidance, autonomy vs. relatedness) were used to identify 4 broad domains of sexual motivations and to develop a measure of specific motives within each of these domains. Data from both college student and community samples are used to demonstrate the psychometric adequacy of these scales and to show that having sex for different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

46
629
6
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 449 publications
(711 citation statements)
references
References 61 publications
46
629
6
8
Order By: Relevance
“…Moreover, it was shown that female adolescents who first experienced sexual intercourse before the age of 16 years had a higher risk of developing depression during adulthood than did those who did so after the age of 16 years [18]. The mechanism behind this may be due in part to the fact that anti-social and depressed adolescents expressed their anti-social and depressed emotions through sex [20]. In the present study, depressive symptoms in adolescents were negatively related or unrelated to their sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that female adolescents who first experienced sexual intercourse before the age of 16 years had a higher risk of developing depression during adulthood than did those who did so after the age of 16 years [18]. The mechanism behind this may be due in part to the fact that anti-social and depressed adolescents expressed their anti-social and depressed emotions through sex [20]. In the present study, depressive symptoms in adolescents were negatively related or unrelated to their sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal associations would suggest additional mechanisms. For example, violence involvement may lead to increases in substance use and sexual behavior over time if engagement in health risk behavior is a means of distracting oneself from or coping with stressful aspects of violence (i.e., stress-response framework [9,[14][15][16][17]). Engagement in substance use and sexual activity with multiple partners may lead to increases in violence involvement over time if these health risk behaviors place adolescents in situations in which violence is more likely to occur (i.e., vulnerability to violence framework [18][19][20]).…”
Section: A Longitudinal Perspectivementioning
confidence: 99%
“…Longitudinal associations would suggest additional mechanisms. For example, violence involvement may lead to increases in substance use and sexual behavior over time if engagement in health risk behavior is a means of distracting oneself from or coping with stressful aspects of violence (i.e., stress-response framework [9,[14][15][16][17] …”
Section: A Longitudinal Perspectivementioning
confidence: 99%
See 2 more Smart Citations